DIDACTIC CONDITIONS FOR CREATING PROBLEMS SITUATIONS IN THE PROCESS OF STUDYING HISTORY - L.V. Zhurba (Academy of Cognitive and Natural Sciences, 2007)
The problem situation is the obligatory component of scientific knowledge. The didactic conditions of création and effective functioning of the problem situations during studying History are opened in the article.